A hydrothermal route for synthesizing highly luminescent sulfur- and nitrogen-co-doped carbon dots as nanosensors for Hg2+. Issue 89 (12th September 2016) - Wang, Chunfeng; Sun, Dong; Chen, Yujuan; Zhuo, Kelei
Abstract : Sulfur- and nitrogen-co-doped carbon dots were synthesized by the one step hydrothermal treatment of pyritinol hydrochloride in the presence of graphene oxide, and could be used as an effective fluorescent probe for the detection of Hg 2+ . Abstract : Carbon dots have attracted tremendous attention due to their excellent properties, such as outstanding photoluminescence, low cytotoxicity, and superior biocompatibility. In this work, a simple and low cost method was developed to synthesize sulfur- and nitrogen-co-doped carbon dots (S/N-CDs) via hydrothermal treatment of pyritinol hydrochloride in the presence of graphene oxide (GO). The S/N-CDs displayed good water solubility, high luminescence stability, excitation-dependent emission, up-conversion photoluminescence, and strong photoluminescence with a quantum yield of ca. 32.2% without complicated surface modifications. In addition, the prepared S/N-CDs were used as a sensitive probe to detect Hg 2+ ions, showing an excellent selectivity and wide linear range. Particularly, the detection limit could reach as low as 1.0 nM.